Aberrant Pyramidal Tract in Comparison with Pyramidal Tract on Diffusion Tensor Tractography: A Mini-Review - Jang, Sungho; Kwak, Soyoung (Frontiers in Neurology, 2017)
The pyramidal tract (PT) is a major neural tract that controls voluntary movements in the human brain. The PT has several collateral pathways, including the aberrant pyramidal tract (APT), which passes through the medial lemniscus location at the midbrain and pons. Diffusion tensor tractography (DTT) allows visualization and estimation of the APT in three dimensions. In this mini-review, eight DTT studies on the APT were reviewed. Two studies for normal subjects reported the prevalence (17 18% of hemispheres) and the different characteristics (different cortical origin, less directionality and fewer neural fibers) of the APT compared with the PT. Six studies reported on the APT in patients with cerebral infarct, traumatic brain injury and cerebral palsy, and suggested that the APT could contribute to motor recovery following brain injury. The research on the APT in patients with brain injury has important implications for neuro-rehabilitation because understanding of the motor recovery mechanism can provide the basis for scientific rehabilitation strategies. Therefore, studies involving various brain pathologies with large numbers of patients on this topic should be encouraged. In addition, further studies are needed on the exact role of the APT in normal subjects.